Potential to induce dentinal cracks during retreatment procedures of teeth treated with “Russian red”: An ex vivo study - Eglė Nedzinskienė; Vytautė Pečiulienė; Jolanta Aleksejūnienė; Rasmutė Manelienė; Saulius Drukteinis; Audronė Jakaitienė (Medicina, 2017)
Objective: The aim of this study was to compare the impact of treatment procedures on roots previously treated with resorcinol–formaldehyde resin and analyze the effectiveness of dye and magnification for the detection of dentin cracks. Materials and methods: Distal roots of 80 permanent first mandibular molars with a single canal were sectioned at 3 mm and 9 mm from the anatomical apex. Two groups were formed according to the method used for root canal penetration: group 1 (K-file and Pro Taper instruments) and group 2 (Ultrasound with Pro Ultra and Pro Taper files). Before and after the completion of procedures, photographs of the roots were taken for examination for cracks or/and infraction lines with two levels of magnification and with or without a dye. Results: In groups 1 and 2, either with dye or without it, there were statistically significant differences (P < 0.001) with more fractures observed in the coronal than in the apical part of specimens. Statistically significant proportional differences regarding the location of fractures were observed at both magnifications. When the dye was used, there were no statistically significant differences between the two magnifications in the detection of cracks. In the specimens where the dye was not used, differences between the groups were statistically significant at both magnifications with more complete and intra-dental fractures observed in group 2. Conclusions: Retreatment methods had a damaging effect on the root dentin of teeth previously treated with resorcinol–formaldehyde resin. At magnification ×16, the efficacy of using the dye for the detection of cracks was higher than detection without the dye.